1991
DOI: 10.1177/004728759103000209
|View full text |Cite
|
Sign up to set email alerts
|

Frequent-Stayer Programs: The Demographic, Behavioral, and Attitudinal Characteristics of Hotel Steady Sleepers

Abstract: This study, based on the results of a survey of hotel guests, describes the extent and operational nature of frequent-stayer programs and examines the statistical profile of hotel guests. Differential demographic, behavioral, and attitudinal characteristics of steady sleepers are provided, and some marketing implications for the hotel industry are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
4

Year Published

1994
1994
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 1 publication
2
51
0
4
Order By: Relevance
“…The list of attributes that people use in selecting a hotel was culled from the literature (Ananth et al, 1992;Atkinson, 1988;Barsky and Labagh, 1992;Callan and Bowman, 2000;Cadotte and Turgeon, 1988;Knutson, 1988;LeBlanc and Nguyen, 1996;Lewis, 1984;McCleary et al, 1993;Rivers et al, 1991;Wilensky and Buttle, 1988) and guest satisfaction surveys distributed by various hotel chains. By considering the primary purpose of their stay in a hotel (i.e., business versus pleasure), respondents were asked to indicate the level of importance they attached to attributes thus obtained on seven-point scales (7=very important, 6=important, 5=slightly important, 4=not sure, 3=slightly unimportant, 2=unimportant and 1=not important at all).…”
Section: Methodsmentioning
confidence: 99%
“…The list of attributes that people use in selecting a hotel was culled from the literature (Ananth et al, 1992;Atkinson, 1988;Barsky and Labagh, 1992;Callan and Bowman, 2000;Cadotte and Turgeon, 1988;Knutson, 1988;LeBlanc and Nguyen, 1996;Lewis, 1984;McCleary et al, 1993;Rivers et al, 1991;Wilensky and Buttle, 1988) and guest satisfaction surveys distributed by various hotel chains. By considering the primary purpose of their stay in a hotel (i.e., business versus pleasure), respondents were asked to indicate the level of importance they attached to attributes thus obtained on seven-point scales (7=very important, 6=important, 5=slightly important, 4=not sure, 3=slightly unimportant, 2=unimportant and 1=not important at all).…”
Section: Methodsmentioning
confidence: 99%
“…Wilensky and Buttle (1988) mentioned that personal services, physical attractiveness, opportunities for relaxation, standard of services, appealing prestige and value for money were significantly evaluated by travelers. Rivers et al (1991) examined the hotel selection decisions of members and non-members of frequent guest programs. Their results illustrated that convenience of location and overall service received the highest ratings.…”
Section: A Concise Review Of Measurement Indicatorsmentioning
confidence: 99%
“…He showed that the 'employee attitude' and 'location' are the first two factors customers emphasize, followed by 'rooms', 'price', 'hotel facilities', 'hotel service', 'parking facilities', and 'food and beverage'. Other studies in the literature suggest that factors including 'location', 'room rate', and 'reputation of the hotel' are also important in affecting customers' choice about ITHs (Barsky, 1992;Barsky & Labagh, 1992;LeBlanc & Nguyen, 1996;McCleary et al, 1993;Pizam & Ellis, 1999;Rivers et al, 1991;Wilensky & Buttle, 1988). Chen et al (2010) investigated the effects of tourist nationalities on the efficiency of ITHs in Taiwan and found out tourists coming from North America, Japan, and Australia have a positive effect on the efficiency of ITHs in Taiwan.…”
Section: Data Sources and Variable Definitionsmentioning
confidence: 99%